The UAE’s Smart Experience of Distance Learning after the Corona Pandemic: Challenges and Solutions: The Emirate of Sharjah – Khorfakkan City as a Model - Al-Naqbi, Huda (Al-Adab Journal, 2025)
The paper dealt with the smart experience of the United Arab Emirates for the distance education system, after the Corona pandemic, challenges and solutions. The paper aimed to identify the great practical experience of distance education, which concerns all segments of society, and to identify the most important challenges and solutions in the UAE. The paper relied on the analytical descriptive approach, as well as on studies and research published in the field of e-learning. Some of the results that had been reached is the teacher’s lack of actual preparation for this sudden transitional phase, as a large percentage of teachers did not have the necessary tools that would enable them to continue with distance education, and some of them did not have sufficient experience in the technical aspects that manage the educational process, Teachers and parents are not ready for the principle of distance learning, the inability of learners in vocational and technical education to learn in virtual classes in some disciplines that require practical applications, workshops and training, Greater difficulties and pressures on parents, which requires more effort from them in the follow-up process. The solutions adopted by the UAE to face these challenges are among the most important: His Highness Sheikh Mohammed bin Rashid Al Maktoum, Vice President of the State, encouraged his call to his students, saying: “Do not stop learning; Science is what makes life, and whoever stops learning stops living.” The ministry worked on the actual training of teachers and students, providing laptops for all teachers and students, the rapid initiatives launched by government agencies and telecommunications companies in the UAE helped to continue work and education remotely, thanks to modern communication systems. Finally, the researcher recommends the necessity of competitive educational services at the local and global levels, keeping pace with technological and technical changes. Addition developing the capabilities of parents in teaching and following up on the evaluation of their children.